THE BRITISH RATIFICATION OF THE UNDERWATER HERITAGE CONVENTION: PROBLEMS AND PROSPECTS. Issue 4 (3rd September 2018) - Roberts, Hayley
Abstract: The UNESCO Convention on the Protection of the Underwater Cultural Heritage 2001 came into force in 2009, providing a much-needed international legal framework for the protection of underwater cultural heritage (UCH). This article explores the reasons why the UK has neglected to ratify the Convention and why accession should now be prioritized. In doing so, the article reconciles the UK's stance with the agreement; moving the State into a position where it can reconsider ratification. In this context, it examines the definition of UCH and the purpose of the Convention, the extension of sovereign immunity for wrecked warships, and the likelihood of creeping coastal State jurisdiction beyond the competences conferred by the UN Convention on the Law of the Sea. This transformative analysis moves forward the debate on these issues and is of international significance to States that have been similarly hesitant to ratify the Convention until now.